3D printing Vegemite and Marmite: Redefining "breadboards". (March 2018) - Hamilton, Charles Alan; Alici, Gursel; in het Panhuis, Marc
Abstract: The ability to use Food Layered Manufacturing (FLM) to fabricate attractive food presentations and incorporate additives that can alter texture, nutrition, color, and flavor have made it widely investigated for combatting various issues in the food industry. For a food item to be FLM compatible, it must possess suitable rheological properties to allow for its extrusion and to keep its 3D printed structure. Here, we present a rheological analysis of two commercially available breakfast spreads, Vegemite and Marmite, and show their compatibility with FLM in producing 3D structures onto bread substrates. Furthermore, we demonstrated that these materials can be used to fabricate attractive food designs that can be used for educational activities. The inherent conductivity of the breakfast spreads was used to print edible circuits onto a "breadboard." Highlights: A rheological study of Vegemite and Marmite is shown. Vegemite and Marmite are compatible with food layered manufacturing at certain temperatures. These breakfast spreads can be used to fabricate attractive food presentations. Vegemite and Marmite are inherently conductive and can be used to print edible circuitry.